Entrepreneurship Education for Professional Growth - Berry, Peyton McKenna (East Carolina University, 2022)
Over the past year, Liz Weil and I have emersed ourselves into the role of becoming an entrepreneur while enrolling in as many opportunities as possible to learn about entrepreneurship education. In Honors 2000 and 3000 we completed customer interviews which provided us the foundation for the business we were building. We enrolled in Entrepreneurship 3500 which was an introduction to entrepreneurship and then Entrepreneurship 4212 which was an Innovation and Opportunity class to learn how to identify the why of your business and how to launch it. We pitched our business created from Honors, Theraplushies, in the Pirate Entrepreneurship Challenge here on campus. We were able to advance to the second round but unfortunately, that is where our journey ended. To continue our learning, we joined the E-passport program in which we earned points to learn more about entrepreneurship through different opportunities. I was able to earn an honors cord from this program as I completed seventy-five points in the program from attending programs from the Small Business Center of NC, events here on campus, and learning from local entrepreneurs.
Keywords: Growth Mindset; Experiential Learning; Personal Branding; Professional Development